Enhancing Physical Education Learning Outcomes Through Game Based Learning Approach in Primary Schools - Wiyarko, Wanuh; Adhi, Bayu Purwo (Juwara: Jurnal Wawasan dan Aksara, 2025)
This study aims to investigate the effectiveness of game-based learning strategies in improving physical education learning outcomes among fifth-grade students. A quasi-experimental research design with a pre-test and post-test control group model was employed. The sample consisted of 40 students from SDN Gondangan, divided equally into experimental and control groups. The experimental group received instruction through a structured game-based learning approach, while the control group followed conventional physical education methods. A purposive sampling technique was used to select participants based on equivalent academic and physical performance backgrounds. Data were collected using standardized physical education achievement tests administered before and after the intervention. Descriptive and inferential statistical analyses, including paired sample t-tests and independent sample t-tests, were conducted to evaluate learning outcomes. The results revealed statistically significant improvements in both groups; however, the experimental group exhibited a significantly greater increase in mean scores compared to the control group (p < 0.001). These findings suggest that game-based learning is more effective in enhancing student engagement and achievement in physical education. The study concludes that integrating game-based strategies into elementary physical education curricula can lead to improved learning outcomes and foster more active, participatory learning environments. These findings offer valuable implications for curriculum development, instructional practice, and future educational research in primary school settings.